Effect of cementation techniques on fracture load of monolithic zirconia crowns - Janne Angen Indergård; Anneli Skjold; Christian Schriwer; Marit Øilo (Medical Journals Sweden, 2021)
Aim The aim of this study was to evaluate the effect of cement on the fracture load of monolithic zirconia crowns with different yttria content (3 and 5 mol%). Methods A total of 62 monolithic zirconia crowns, 40 3Y-zirconia crowns (Prettau® Zirconia, Zirkonzahn) and 22 5Y-zirconia crowns (Prettau® 4 Anterior®, Zirkonzahn) were produced to a shallow chamfer molar preparation. The 3Y-crowns were divided into four groups and attached to composite abutment duplicates (SDR® flow+, Dentsply DeTrey GmbH) using the following four cementation techniques; (1) Self-adhesive resin-based cement, (2) Pre-treatment with air-abrasion and self-adhesive resin-based cement, (3) Zinc phosphate cement, (4) Glass-ionomer cement. The 5Y-crowns were divided into two groups and attached to the duplicates with; (1) Self-adhesive resin-based cement, or (2) Air-abrasion pre-treatment and self-adhesive resin-based cement. All crowns were loaded axially (0.5 mm/min) on the occlusal surface until fracture occurred. Results Among the 3Y-zirconia groups, the zinc phosphate cement group fractured at lower loads compared to the resin-based cement groups, with and without air-abrasion, (p < .012). Among the 5Y-groups the air-abraded crowns fractured at statistically significant lower loads compared to the untreated crowns (p < .028). Load at fracture values were significantly different between the two zirconia materials (p < .001), with fracture loads ranging from 3873 to 7500 N in the 3Y-groups, and 2100 to 4948 N in the 5Y-groups. Conclusions Resin-based cementation increased the fracture load compared to non-adhesive cementation. The 3Y-crowns fractured at almost twice the loads of the 5Y-crowns. Pre-treatment with air abrasion reduced the strength of the 5Y-crowns only, showing the importance of differentiating the treatment of the two materials.